Math 215 Spring 2010 Assignment 8 You are highly recommended to own a textbook, Boyce-DiPrima or another, to see a comprehensive treatment of the subjects and more examples. §7.7: 6, 7, 12, §7.8: 1c, 4c, 8a, §7.9: 4, 6, 11 µ ¶ −1 −4 • (§7.7: 6) Find a fundamental matrix for x = x. Also find the fundamental 1 −1 matrix Φ(t) satisfying Φ(0) = I. 0 Answer. Setting det(A − rI) = r2 + 2r + 5 = 0, the eigenvalues are −1 ± 2i. For r = −1 − 2i, the eigenvector equation (A − rI)ξ = 0 reduces to ξ1 + 2iξ2 = 0. We can take ξ = (−2i, 1)T . Thus µ ¶ µ ¶ µ ¶ −2i (−1−2i)t (1) −t −2 sin 2t −t −2 cos 2t x (t) = e =e + ie . 1 cos 2t − sin 2t We can take µ ¶ −2 sin 2t −2 cos 2t Ψ(t) = e . cos 2t − sin 2t µ ¶ µ ¶ 0 2 0 −2 1 −1 , we have Since Ψ(0) = with Ψ(0) = 2 −1 0 1 0 µ ¶ 1 −t 2 cos 2t −4 sin 2t −1 . Φ(t) = Ψ(t)Ψ(0) = e sin 2t 2 cos 2t 2 −t µ ¶ 5 −1 • (§7.7: 7) Find a fundamental matrix for x = x. Also find the fundamental 3 1 matrix Φ(t) satisfying Φ(0) = I. 0 Answer. Setting det(A − rI) = r2 − 6r + 8 = 0, the eigenvalues are 2, 4. For r = 2, the eigenvector equation (A − rI)ξ = 0 reduces to 3ξ1 − ξ2 = 0. We can take ξ = (1, 3)T . For r = 4, the two equations in (A − rI)ξ = 0 reduce to ξ1 − ξ2 = 0. We can take ξ = (1, 1)T . Thus µ ¶ µ 2t ¶ µ ¶ µ 4t ¶ 1 2t e 1 4t e (1) (2) x (t) = e = , x (t) = e = 4t . 3 3e2t 1 e We can take µ ¶ e2t e4t Ψ(t) = . 3e2t e4t µ ¶ µ ¶ 1 1 1 −1 1 −1 Since Ψ(0) = with Ψ(0) = − 2 , we have 3 1 −3 1 µ ¶ 1 −e2t + 3e4t e2t − e4t . Φ(t) = Ψ(t)Ψ(0)−1 = 2 −3e2t + 3e4t 3e2t − e4t • (§7.7: 12) Solve the initial value problem µ ¶ −1 −4 0 x = x, 1 −1 µ ¶ 3 x(0) = 1 by using the fundamental matrix Φ(t) found in problem 6. Answer. We have µ ¶ µ ¶µ ¶ µ ¶ 1 −t 2 cos 2t −4 sin 2t 3 3 −t 3 cos 2t − 2 sin 2t x(t) = Φ(t) = e =e . 3 1 sin 2t 2 cos 2t 1 2 2 sin 2t + cos 2t µ ¶ 3 −4 • (§7.8: 1c) Find the general solution of x = x. 1 −1 0 Answer. Setting det(A − rI) = r2 − 2r + 1 = 0, the eigenvalues are 1, 1. For r = 1, the eigenvector equation (A − rI)ξ = 0 reduces to ξ1 − 2ξ2 = 0. We can take ξ = (2, 1)T and the first solution is x(1) (t) = ξet . The generalized eigenvector satisfies (A−I)η = ξ, which reduces to η1 −2η2 = 1. If η2 = k where k is an arbitrary constant, then η2 = 1 + 2k and η = (1, 0)T + kξ. A second solution is x(2) (t) = (tξ + η)et . The general solution is µ ¶ µ ¶ 2 t 2t + 1 t x(t) = c1 x(1) (t) + c2 x(2) (t) = c1 e + c2 e. 1 t In the above we have set k = 0 since it can absorbed into c1 . µ ¶ −3 5/2 0 • (§7.8: 4c) Find the general solution of x = x. −5/2 2 Answer. Setting det(A − rI) = r2 + r + 1/4 = 0, the eigenvalues are −1/2, −1/2. For r = −1/2, the eigenvector equation (A − rI)ξ = 0 reduces to ξ1 − ξ2 = 0. We can take ξ = (1, 1)T and the first solution is x(1) (t) = ξe−t/2 . The generalized eigenvector equation (A − rI)η = ξ reduces to η1 − η2 = −2/5. If η1 = k where k is an arbitrary constant, then η2 = 2/5 + k and η = (0, 2/5)T + kξ. A second solution is x(2) (t) = (tξ + η)e−t/2 . The general solution is µ ¶ µ ¶ 1 −t/2 t x(t) = c1 x(1) (t) + c2 x(2) (t) = c1 e + c2 e−t/2 . 1 t + 2/5 In the above we have set k = 0 since it can absorbed into c1 . 2 µ ¶ −5/2 3/2 x, • (§7.8: 8a) Solve the initial value problem x = −3/2 1/2 0 ¶ 3 . −1 µ x(0) = Answer. The characteristic equation is det(A − rI) = r2 + 2r + 1 = 0, with a single root −1. For r = −1, the eigenvector equation (A − rI)ξ = 0 reduces to ξ1 − ξ2 = 0. We can take ξ = (1, 1)T and the first solution is x(1) (t) = ξe−t . The generalized eigenvector satisfies (A − rI)η = ξ, which reduces to η1 − η2 = −2/3. If η1 = k where k is an arbitrary constant, then η2 = 2/3+k and η = (0, 2/3)T +kξ. A second solution is x(2) (t) = (tξ + η)e−t . The general solution is µ ¶ µ ¶ 1 −t t (1) (2) x(t) = c1 x (t) + c2 x (t) = c1 e + c2 e−t . 1 t + 2/3 In the above µ ¶ we have µ set ¶ k µ= 0¶since it can absorbed into c1 . The initial condition 1 0 3 gives c1 + c2 = . Thus c1 = 3, c2 = −6, and 1 2/3 −1 µ ¶ 3 − 6t e−t . −1 − 6t x(t) = µ ¶ µ −2t ¶ 1 1 e • (§7.9: 4) Find the general solution of x = x+ . 4 −2 −2et µ ¶ µ ¶ 1 2t 1 Hint: You can use xc (t) = c1 e + c2 e−3t from §7.5 #4. 1 −4 0 Answer. is Since g(t) = (e−2t , −2et )T involves exponential functions only, a first guess xp (t) = ae−2t + bet . It requires no revision since e−2t and et do not appear in xc (t). Substituting it into the equation, −2ae−2t + bet = Aae−2t + Abet + g(t). Thus µ ¶ −1 (A + 2)a = , 0 µ ¶ 0 (A − 1)b = . 2 We can solve a = (0, −1)T and b = (1/2, 0)T , and thus µ ¶ µ ¶ µ ¶ µ ¶ 1 2t 1 0 1/2 t −3t −2t x(t) = xc (t) + xp (t) = c1 e + c2 e + e + e. 1 −4 −1 0 The problem can be done by other methods. 3 µ −1 ¶ µ ¶ t −4 2 , t > 0. x+ • (§7.9: 6) Find the general solution of x = −1 2 −1 2t + 4 0 Answer. The characteristic equation is det(A − rI) = r2 + 5r = 0, with roots r = 0, −5. Their corresponding eigenvectors are (1, 2)T and (−2, 1)T . Set µ ¶ µ ¶ µ ¶ 1 1 2 1 −2 0 0 −1 T = , T = , D= . 2 1 0 −5 5 −2 1 We have AT = T D. Setting y = T −1 x and h(t) = T −1 g(t), the transformed system is 1 8 4 y10 = + , y20 = −5y + . t 5 5 Their solutions are 8 4 y1 = c1 + ln t + t, y2 (t) = c2 e−5t + . 5 25 Thus µ ¶ ¶ µ ¶ µ 8 1 −2 −5t ln t + 58 t − 25 . + c2 e + x(t) = T y(t) = c1 4 2 1 2 ln t + 16 5 t + 25 µ ¶ µ ¶ 2 −5 0 • (§7.9: 11) Find the general solution of x = x+ , 0 < t < π. 1 −2 cos t µ ¶ µ ¶ 2 cos t − sin t cos t + 2 sin t Hint: You can use xc (t) = c1 + c2 from §7.6 #3. cos t sin t 0 Answer. It follows from the formula of xc (t) a fundamental matrix µ ¶ 2 cos t − sin t cos t + 2 sin t Ψ(t) = . cos t sin t We have det Ψ(t) = −1 and µ ¶ µ ¶ − sin t cos t + 2 sin t cos2 t + 2 cos t sin t −1 −1 Ψ(t) = , Ψ(t) g(t) = . cos t −2 cos t + sin t −2 cos2 t + sin t cos t µ ¶ µ1 ¶ Z c1 cos t sin t + 21 t + sin2 t −1 2 Ψ(t) g(t)dt = + . c2 − cos t sin t − t + 21 sin2 t Thus µ ¶ µ1 ¶ c1 cos t sin t + 12 t + sin2 t 2 x(t) = Ψ(t) + Ψ(t) c2 − cos t sin t − t + 21 sin2 t µ ¶ µ ¶ µ µ 5¶ ¶ c1 0 0 −2 = Ψ(t) + 1 t cos t + t sin t + 1 . c2 −1 2 2 sin t µ ¶ µ ¶ µ ¶ 0 −5/2 c The last term 1 can be replaced by cos t by a different choice of 1 . sin t −1 c2 2 Remark. To use the method of undetermined coefficient, since g(t) “resonants” with the eigenvalues ±i, one assumes xp = (a + bt) cos t + (c + dt) sin t . 4